Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

I Proving Euclidian Algorithm

  1. Nov 12, 2016 #1

    In this video, at 5:35 He has d/(a-qb) for the first part. I was not sure how he got that. Why is it not d/(a+qb)?

    Because d/a and d/bc implies d/(a+bc)

    Why does +bc become negative?
  2. jcsd
  3. Nov 12, 2016 #2


    User Avatar
    2017 Award

    Staff: Mentor

    It divides both.

    If a=x*d and b=y*d then a-qb=x*d - q*y*d = (x-qy)*d and also a+qb=x*d + q*y*d = (x+qy)*d
    The second formula less useful for the next step, however, because it would make numbers larger.
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook

Have something to add?
Draft saved Draft deleted